A simplified laboratory approach for isolating M. oryzae spores from rice samples infected with multiple pathogens - Suvanthini, T.; Fernando, H.N.S.; Silva, J.N.; Kottearachchi, N.S.; Weerasena, O.V.D.S.J. (ELSEVIER, 2024)
A method for separating M. oryzae from rice samples infected with multiple pathogens using basic laboratory equipment is described. We conducted a series of experiments to obtain a single spore of M. oryzae. This method can also be used to isolate spores from other fungal species.Section snippets CRediT authorship contribution statement S. Terensan: Writing – review & editing, Writing – original draft, Visualization, Validation, Software, Methodology, Investigation, Funding acquisition, Formal analysis, Data curation, Conceptualization. H.N.S. Fernando: Validation, Resources, Methodology. J.N. Silva: Validation, Methodology. N.S. Kottearachchi: Writing – review & editing, Supervision, Methodology, Conceptualization. O.V.D.S.J. Weerasena: Writing – review & editing, Supervision, Methodology, Conceptualization. ... Declaration of competing interest The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper. ... Acknowledgements We extend our gratitude to the Pathology Division team at the Rice Research and Development Centre, Bombuwala, Sri Lanka, for their invaluable technical support and for supplying the positive blast diseased samples, which greatly aided us in honing our isolation techniques. Our sincere appreciation goes to Mr. S. Sivaneson of the Regional Rice Research Station, Paranthan, Sri Lanka, for his assistance in collecting diseased samples. Additionally, we acknowledge the generous contribution of ...
Keywords: Rice blast; Magnaporthe oryzae; Spore isolation; Conidia; Multiple infection